The CDA TM book - Boone, Keith W. (Springer, 2011)
Clinical documentation is used throughout healthcare to describe care provided to patient, communicate essential information between healthcare providers and maintain medical records.  The CDA Book describes the HL7 Clinical Document Architecture Release 2.0 standard, a standard format for clinical documentation.  It is thus intended for Healthcare Informaticists and IT developers, analysts and architects developing Healthcare applications working with all types of clinical documents. The Clinical Document Architecture (CDA) is a common container for assembly of structured and unstructured information that does not require creating numerous standards for individual document types. What has been missing to date is the educational materials to make CDA accessible to everyone. This book contains the documentation, samples, and guidance needed to successfully implement CDA in real world applications.  It will accelerate adoption of CDA as a means to exchange structured data elements that not only capture the thought process of the encounter for care coordination but also can be stored as individual data elements for population health, research, and decision support. John D. Halamka MD, Chief Information Officer at Harvard Medical School.